2016
DOI: 10.1016/j.jadohealth.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mental Health Symptoms Across Lesbian, Gay, Bisexual, and Questioning Youth in Primary Care Settings

Abstract: Findings highlight varying level of risk across subgroups of LGBQ youth and suggest the importance of considering LGBQ groups separately in the context of a behavioral health assessment, especially for females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
2
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 36 publications
(50 reference statements)
7
67
2
21
Order By: Relevance
“…27 Second, despite a fairly large sample, sexual minority subgroups were small and could not be disaggregated for analyses. In light of growing research suggesting diversity among sexual minority subgroups, 1,3 future research is needed to better understand the unique health care needs of lesbian, gay, bisexual, and questioning adolescents. Third, although the current analytic sample is largely similar to the Wave 2 NEXT sample in terms of sample characteristics, attrition and missing data which varied by race/ethnicity and family affluence could have introduced bias to the analytic sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Second, despite a fairly large sample, sexual minority subgroups were small and could not be disaggregated for analyses. In light of growing research suggesting diversity among sexual minority subgroups, 1,3 future research is needed to better understand the unique health care needs of lesbian, gay, bisexual, and questioning adolescents. Third, although the current analytic sample is largely similar to the Wave 2 NEXT sample in terms of sample characteristics, attrition and missing data which varied by race/ethnicity and family affluence could have introduced bias to the analytic sample.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are particularly important in the context of past research suggesting that sexual orientation-related health disparities may be more pronounced among females. 13,38 Structural and policy approaches aimed at increasing the rates of annual routine physical check-up could further reduce sexual orientation-related health disparities among female adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been insufficient attention paid to understanding how variations in sexual identity shape needs in relation to – and experiences of – alcohol and mental health treatment 28 . Instead of treating LBQ women as a homogenous sub‐population, it has been suggested that LBQ sub‐groups should be considered separately in the context of their healthcare needs 17 . This paper aims to address this gap by focusing on how differences in sexual identity among LBQ women shaped treatment experience and needs.…”
mentioning
confidence: 99%
“…As Phyllis pointed out, when these platforms' features fell short and women in this study were unable to modulate their identities as they desired, they developed workarounds or migrated to new platforms altogether. Practices of identity modulation, which contribute to the formation of networked publics where queer women can see their identities represented and access social support, are especially important when studies still report higher rates of anxiety, depression, traumatic stress, and suicidal ideation for lesbian and bisexual women than for heterosexual women (Shearer et al, 2016). Queer women's networked publics can increase their visibility, offer routes for attaining personal and professional aims, and draw heteronormative biases into question.…”
Section: Resultsmentioning
confidence: 99%